Biological recycling theory: a cyclic network framework for evolutionary innovation and recovery - Mesallum, Sameh (Frontiers in Ecology and Evolution, 2025)
IntroductionLife’s macroevolutionary patterns—rapid post-extinction recoveries and bursts of novelty—are not fully explained by mutation and vertical descent alone. I introduce Biological Recycling Theory (BRT), a cyclic, network-based framework.MethodsAn agent-based model compared four scenarios (classical, cryptic-only, HGT-only, full BRT), with extinction pulses and explicit constraints on DNA uptake/compatibility; code and runs are archived.ResultsUnder 50% extinction, BRT restored ~90% of pre-event diversity in ~⅓ fewer generations than classical models and yielded ~3,600 novel genotype combinations (vs. ~2,800 cryptic-only; ~700 HGT-only; ~0 mutation-only). Longer eDNA half-life increased diversity retention and innovation.DiscussionBRT integrates balancing selection, cryptic genetic variation, and genetic recycling via HGT/eDNA to expand the effective genetic search space across time, offering a testable framework for macroevolutionary resilience.ConclusionEvolution is better modeled as a cyclic network, where alleles circulate across populations, environments, and time, complementing Darwinian microevolution.